Epidemiological Features and Antibiotic Resistance Patterns of Haemophilus influenzae Originating from Respiratory Tract and Vaginal Specimens in Pediatric Patients - Li, Jian-Ping; Hua, Chun-Zhen; Sun, Li-Ying; Wang, Hong-Jiao; Chen, Zhi-Min; Shang, Shi-Qiang (Journal of pediatric & adolescent gynecology, 2017)
Haemophilus influenzae (H. influenzae) is a common pathogen of respiratory tract infections in children, however, as a possible cause of vulvovaginitis in prepubertal girls, its epidemiological features, antibiotic-resistance patterns, and treatment are seldom noted. Specimens obtained from patients were inoculated on Haemophilus selective medium; and drug-sensitivities tests were determined using the disk diffusion method. A cefinase disk was used to detect β-lactamase. A total of 610 H. influenzae strains, 81.6% (498/610) from the respiratory tract and 18.0% (110/610) from the vagina, were identified in the Children's Hospital in 2015. The age of the children with respiratory tract strains were significantly younger than those with vaginal strains (P < .001). The H. influenzae isolation rate in May was the highest. The β-lactamase positive rate was 51.5% (314/610), and 52.5% (320/610) were resistant to ampicillin. The susceptibilities rates to cefuroxime, ampicillin/sulbactam, cefotaxime, clarithromycin, and sulfamethoxazole-trimethoprim were 72.1% (440/610), 95.9%, 96.4% (588/610), 81.8% (499/610), and 36.4% (222/610), respectively. Higher resistance to ampicillin, cefuroxime, clarithromycin, and sulfamethoxazole-trimethoprim were found in respiratory tract strains, compared with vaginal strains (P < .05). All of the patients with H. influenzae in the respiratory tract were cured with oral or intravenous β-lactam antibiotics. Of all patients with vaginal strains, 50% (55/110) were cured with topical ofloxacin gel, and 44.5% (49/110) were cured with oral β-lactam antibiotics. The drug-resistance rates of H. influenzae isolated from vagina were lower than those from the respiratory tract. Topical ofloxacin gel or oral β-lactam antibiotics are effective treatments to eliminate the H. influenza causing infection in the vagina.